Association between nomophobia and learning performance among undergraduate students: the mediating role of depression and anxiety - Abukhanova, Azhar; Almukhambetova, Bibigul; Mamekova, Assem; Spatay, Aygul; Danikeyeva, Aigul (Frontiers in Education, 2024)
Background: There is a gap in the existing literature concerning the connection between nomophobia and diminished academic performance, potentially influenced by anxiety and depression. The present study aimed to examine the relationship between undergraduate students' nomophobia and learning outcomes, and whether depression and/or anxiety mediate this potential link.Methods: A quantitative cross-sectional survey design was employed. Nomophobia, anxiety, and depression were measured in 307 undergraduate students using validated self-report questionnaires. Learning performance was assessed based on participants' grade point averages. Correlation analysis and mediation analysis were conducted to test the hypotheses.The Pearson correlation analysis and multiple parallel mediation modeling suggest that anxiety plays a significant role as a causal pathway through which nomophobic behavior leads to lower grades among university students compared to their less anxious peers. Depression had no significant mediation effect.The findings support the notion that nomophobia is linked to poor academic achievement. The detrimental impact of nomophobia on learning performance appears to be more closely tied to anxiety rather than depression. This research contributes to the understanding of the complex interplay between technology use, psychological well-being, and educational outcomes in the higher education context. The study's implications include the validation of the measurement scales in a non-English population and the recognition of the influence of technology on mental health and academic outcomes.